Suspects. Series five [videorecording (DVD)] - Molony, Damien; Ashitey, Clare-Hope, 1987-; Murray, James, 1975- (Acorn, 2017)
DS Jack Weston and DC Charlie Steele are shocked when their boss, DI Martha Bellamy, is shot dead in her home. DCI Daniel Drummond joins Jack and Charlie to lead the investigation into Martha's murder, also bringing in detectives Alisha Brooks and Gary Roscoe. The new team soon realizes that Martha's murder could be connected to a cold case she was investigating. Could one of those suspects have killed her?